2017
DOI: 10.1123/ijspp.2015-0712
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Whole-Body External Loading and Body-Worn Accelerometry During Team-Sport Movements

Abstract: Purpose: The aim of this study was to investigate the relationship between wholebody accelerations and body-worn accelerometry during team sports movements. Methods: Twenty male team sport players performed forward running, and anticipated 45° and 90° side-cuts at approach speeds of 2, 3, 4 and 5 m·s -1 . Wholebody Centre of Mass (CoM) accelerations were determined from ground reaction forces collected from one foot-ground-contact and segmental accelerations were measured from a commercial GPS/accelerometer un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(120 citation statements)
references
References 20 publications
4
110
3
3
Order By: Relevance
“…Regarding a(t), a total of 6438.1 g/min was found in the present study, but higher cumulative data of 8040 g/min has been recorded in other studies in a specific training soccer circuit [38]; therefore there are not enough references using a(t) in soccer play. Finally, it is difficult to compare the data on PL RE obtained in this research because the ZXY SportTracking device used fits the IMU on the waist, and other systems fit the units at the T2−T4 level between the scapulae; due to this fact, the values obtained are lower than those published previously [17] because the workload resulting from lumbar segments tends to be higher than those assessed in thoracic segments [20,38,56,57]. In this sense, previous research realized by Nedergaard et al [56] reported that a body-worn accelerometer only measures the acceleration of the segment that it is attached to, therefore, worse agreements could be expected with the other ABELIs due to the different measurement location.…”
Section: Discussionmentioning
confidence: 73%
“…Regarding a(t), a total of 6438.1 g/min was found in the present study, but higher cumulative data of 8040 g/min has been recorded in other studies in a specific training soccer circuit [38]; therefore there are not enough references using a(t) in soccer play. Finally, it is difficult to compare the data on PL RE obtained in this research because the ZXY SportTracking device used fits the IMU on the waist, and other systems fit the units at the T2−T4 level between the scapulae; due to this fact, the values obtained are lower than those published previously [17] because the workload resulting from lumbar segments tends to be higher than those assessed in thoracic segments [20,38,56,57]. In this sense, previous research realized by Nedergaard et al [56] reported that a body-worn accelerometer only measures the acceleration of the segment that it is attached to, therefore, worse agreements could be expected with the other ABELIs due to the different measurement location.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, higher PlayerLoad TM has been reported during striding compared to sprinting during a soccer simulation protocol (Barreira et al 2016). Although the validity of whole body loading assessed using microtechnology has been questioned (Nedergaard et al 2017), the metric may be useful when prescribing training for youths at different stages of their physical development. The increased mechanical load associated with combination running may be an unwanted outcome, especially given the paucity of information surrounding appropriate loading patterns for young athletes (Gabbett et al 2014;van der Sluis et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…11,13,17 These findings concur with existing research that show GPS-mounted triaxial accelerometers placed at C7 cannot accurately identify load experienced at the lower extremities when performing functional movements, 18 and that body-worn tri-axial accelerometery can only measure the acceleration of the segment at which it is located. 19 The clinical interpretation of acceleration data collected at C7 should therefore be treated with caution, where inferences are made based on the magnitude of load.…”
Section: The Influence Of Gps Locationmentioning
confidence: 99%